Human sweat odour conjugates in human milk, colostrum and amniotic fluid - Hartmann, Constanze; Doucet, Sèbastien; Niclass, Yvan; Dittrich, Ralf; Cupisti, Susanne; Schaal, Benoist; Büttner, Andrea; Starkenmann, Christian (Food Chemistry, 2012)
Using ultra performance liquid chromatography-mass spectrometry we identified for the first time glutamine-N-alpha-conjugates of the fatty acids (E)/(Z)-3-methylhex-2-enoic acid and (R)/(S)-3-hydroxy-3-methylhexanoic acid as well as cysteinylglycine-S-conjugates of (R)/(S)-3-methyl-3-sulphanylhexan-1-ol and (R)/(S)-3-sulphanylhexan-1-ol as constituents of human milk and colostrum. The glutamine-N-alpha-conjugates were detected also in human amniotic fluids. The mean values of glutamine-N-alpha-conjugate of (R)/(S)-3-hydroxy-3-methylhexanoic acid were highest in colostrums with a range of <0.1-382 mu g/kg, followed by the mature human milk with values from <0.1 to 39.6 mu g/kg for defatted milk, and 0.8-7.0 mu g/kg in amniotic fluids. The cysteinylglycine-S-conjugate of (R)/(S)-3methyl-3-sulphanylhexan-1-ol were detected in the range of 2-24 ng/kg in human milk, and 7-101 ng/kg in colostrums. Our data demonstrate that concentrations in human milk vary between individuals, and with lactation period as the mean concentrations of the glutamine conjugates in colostrums were elevated in comparison to mature milk and the concentrations of acid precursors were close to 10 times higher. Further, these precursors were not detected in cow milk. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cysteinylglycine-S-conjugate; Glutamine-N-alpha-conjugate; Human milk; Amniotic fluid; Odour precursor